Efeitos do Ethrel® sobre a produção e atividade das invertases em seringueira, clone RRIM 600, cultivada em Nepomuceno-MG - Domiciano, Débora (2015)
The rubber tree, Hevea brasiliensis (Willd. ex. Adr. de Juss.) Is the main species of its genus economically exploited for the production of natural rubber. Among the rubber tree clones, RRIM 600 stands out for its good productivity and adapt to various weather patterns. Widely cultivated in Minas Gerais the RRIM 600 clone have shown good adaptation to this region, mainly characterized by having a well-defined dry season and therefore unfavorable to the development of the fungus evil leaves (Microcyclus ulei (P. Henn.) Arx.), limiting factor to the expansion of rubber trees in Brazil. In order to understand the physiological aspects related to productivity RRIM 600 clone grown in the southern region of Minas Gerais, were assessed the effects of stimulation with Ethrel® on the enzymes involved in sucrose hydrolysis process in tapping tissues. It was also evaluated relationship of the stimulation of latex based on yields of the biochemical characteristics, based on the activities of enzymes neutral cytosol invertase, vacuolar acid invertase and cell wall invertase, after two periods of application of the stimulant. For the analyzes, were used bark of caule samples collected from October 2014 to January 2015. The study was conducted on commercial planting of rubber tree eight years, in municipality of Nepomuceno-MG. Production data were obtained in the respective months, by tapping the bark in system ½ spiral (S) between 2 days to 3 days (d2 / d3), productivity was expressed as the ratio of dry rubber production in grams (gm) by area of the tapping section. The productivity was expressed by the ratio of dry rubber (bs) production gm to area tapping panel (cm2) and (bs)/plant /tapping gm. It was also given the obstruction index of latex vessel. The evaluated biochemical characteristics, the activities of enzymes vacuolar acid invertase, neutral cytosol invertase showed the significant increase in plants that received treatment with stimulant. Similar behavior evaluated for production bs/plant/tapping in grams and to the production area by tapping panel, whereas the index obstruction in the trees stimulated with Ethrel® decreased. The data confirm the positive correlation between the uses of stimulants the basis of ethylene and productive performance of clone RRIM 600.